Efficient design and scalable control for store-and-forward capable optical transport networks - Lee, Chankyun; Rhee, June-Koo Kevin (Journal of optical communications and networking, 2017)
The increasingly bursty nature of delaytolerable content delivery services requires new design and control perspectives in state-of-the-art end-to-end bufferless transport networks. Store-and-forward capable networked buffers in end-to-end lightpath networks enable an optical delay-tolerant networking (DTN) service that efficiently improves the capacity of optical networks by time-domain traffic shaping. We model an architecture of the optical DTN and asymptotically analyze the blocking probability performance as a function of the buffer node ratio. We propose a novel buffer node location algorithm by suggesting a bottleneckness centrality measure and evaluate the algorithm by comparing it with reference facility location algorithms. Rigorous simulation studies over practical core network topologies, as a function of networking cost, reveal higher performance of the optical DTN model as well as the proposed network-planning algorithms.